Selling off the family silver: the politics of privatization in the OECD 1990-2000 - Herbert Obinger; Reimut Zohlnhöfer (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2005)
The 1990s have witnessed unprecedented attempts at privatizing state owned enterprises in virtually all OECD democracies. This contribution analyzes the differences in the privatization proceeds raised by EU- and OECD-countries between 1990 and 2000. It turns out that privatizations are part of a process of economic liberalization in previously highly regulated economies as well as a reaction to the fiscal policy challenges imposed by European integration and the globalization of financial markets. In addition, institutional pluralism and union militancy yield significant and negative effects on pri-vatization proceeds. Partisan differences only emerge if economic problems are moderate, while intense economic, particularly fiscal problems foreclose differing partisan strategies.
Keywords: 330; Privatisierung; Öffentliches Unternehmen; OECD-Staaten